Development of pico-satellite sun sensors - Ye, Htwe. (2010)
Due to recent miniaturization of electronic components and computer systems, the nano-satellite (below 10kg) and pico-satellite (below 1kg) becomes more easily achievable and the cost of them also becomes affordable by Universities. Starting from this year, NTU also kicks start the pico-satellite project to encourage multi-disciplinary teamwork and opportunities to engage in real-world engineering projects among the engineering undergraduates and professors. Among several projects under pico-satellite, this thesis will deal with “Sun Sensors”. The sun sensors are used for providing a vector measurement to the Sun. Since they are lightweight, small size and low power consuming, almost all small satellites employ the Sun Sensor as an ADCS component. This project would involve studying the various types of the sun sensors. The next stage would involve designing a particular sun sensor. The sun sensor was then implemented, tested and then transferred onto a printed circuit board. The signal processing circuit bought from supplier was also tested using the same set up and used as a reference. Lastly the sun sensor circuit was integrated using a microchip to be more standalone. Finally, this thesis reveals possible future works that can be carried out to achieve a more accurate and standalone sun sensor network. The challenges, results, products and recommendations obtained through this final year project would assist in successful completion of the NTU Pico-satellite project in the near future.